APPLICATION OF FUZZY NEURAL NETWORKS - Kurbanov Bakhtier Tokhtaevich (Western European Studies, 2024)
The article provides brief information about artificial intelligence and neural networks. The results of implanting chips into the human brain are presented. The concepts of fuzzy neural networks are defined. Information is provided about fuzzy mathematics, fuzzy logic and fuzzy sets, on the basis of which fuzzy neural networks are formed. An example of the use of fuzzy neural networks based on the use of fuzzy logic methods is given.
Keywords: Neural networks; fuzzy mathematics; fuzzy logic